A Variation in FGF14 Is Associated with Downbeat Nystagmus in a Genome-Wide Association Study - Michael Strupp; Stephan Maul; Bettina Konte; Annette M. Hartmann; Ina Giegling; Sophia Wollenteit; Katharina Feil; Dan Rujescu (The Cerebellum, 2020)
Downbeat nystagmus (DBN) is a frequent form of acquired persisting central fixation nystagmus, often associated with other cerebellar ocular signs, such as saccadic smooth pursuit or gaze-holding deficits. Despite its distinct clinical features, the underlying etiology of DBN often remains unclear. Therefore, a genome-wide association study (GWAS) was conducted in 106 patients and 2609 healthy controls of European ancestry to identify genetic variants associated with DBN. A genome-wide significant association ( p < 5 × 10 −8 ) with DBN was found for a variation on chromosome 13 located within the fibroblast growth factor 14 gene (FGF14). FGF14 is expressed in Purkinje cells (PCs) and a reduction leads to a decreased spontaneous firing rate and excitability of PCs, compatible with the pathophysiology of DBN. In addition, mutations in the FGF14 gene cause spinocerebellar ataxia type 27. Suggestive associations ( p < 1 × 10 −05 ) could be detected for 15 additional LD-independent loci, one of which is also located in the FGF14 gene. An association of a region containing the dihydrofolate reductase (DHFR) and MutS Homolog 3 (MSH3) genes on chromosome 5 was slightly below the genome-wide significance threshold. DHFR is relevant for neuronal regulation, and a dysfunction is known to induce cerebellar damage. Among the remaining twelve suggestive associations, four genes (MAST4, TPPP, FTMT, and IDS) seem to be involved in cerebral pathological processes. Thus, this GWAS analysis has identified a potential genetic contribution to idiopathic DBN, including suggestive associations to several genes involved in postulated pathological mechanisms of DBN (i.e., impaired function of cerebellar PCs).

No Association Between NRG1 and ErbB4 Genes and Psychopathological Symptoms of Schizophrenia - Sarah Tosato; Martina Zanoni; Chiara Bonetto; Federica Tozzi; Clyde Francks; Elisa Ira; Simona Tomassi; Mariaelena Bertani; Dan Rujescu; Ina Giegling; David St Clair; Michele Tansella; et al. (NeuroMolecular Medicine, 2014)

Impact of COMT genotype on serotonin-1A receptor binding investigated with PET - Pia Baldinger; Andreas Hahn; Markus Mitterhauser; Georg S. Kranz; Marion Friedl; Wolfgang Wadsak; Christoph Kraus; Johanna Ungersböck; Annette Hartmann; Ina Giegling; Dan Rujescu; Siegfried Kasper; et al. (Brain Structure and Function, 2014)

Lack of association between 71 variations located in candidate genes and response to acute haloperidol treatment - Ina Giegling; Antonio Drago; Martin Schäfer; Annette M. Hartmann; Thomas Sander; Mohammad Reza Toliat; Hans-Jürgen Möller; Diana De Ronchi; Hans H. Stassen; Dan Rujescu; Alessandro Serretti (Psychopharmacology, 2011)

Erratum to: Evidence of statistical epistasis between DISC1, CIT and NDEL1 impacting risk for schizophrenia: biological validation with functional neuroimaging - Kristin K. Nicodemus; Joseph H. Callicott; Rachel G. Higier; Augustin Luna; Devon C. Nixon; Barbara K. Lipska; Radhakrishna Vakkalanka; Ina Giegling; Dan Rujescu; David St. Clair; Pierandrea Muglia; Yin Yao Shugart; et al. (Human Genetics, 2010)

Evidence of statistical epistasis between DISC1, CIT and NDEL1 impacting risk for schizophrenia: biological validation with functional neuroimaging - Kristin K. Nicodemus; Joseph H. Callicott; Rachel G. Higier; Augustin Luna; Devon C. Nixon; Barbara K. Lipska; Radhakrishna Vakkalanka; Ina Giegling; Dan Rujescu; David St. Clair; Pierandrea Muglia; Yin Yao Shugart; et al. (Human Genetics, 2010)

Evidence for statistical epistasis between catechol-O-methyltransferase (COMT) and polymorphisms in RGS4, G72 (DAOA), GRM3, and DISC1: influence on risk of schizophrenia - Kristin K. Nicodemus; Bhaskar S. Kolachana; Radhakrishna Vakkalanka; Richard E. Straub; Ina Giegling; Michael F. Egan; Dan Rujescu; Daniel R. Weinberger (Human Genetics, 2007)